Impacts of black granite quarrying on household income and food security: a case study of Mutoko district in Zimbabwe - Sibanda, Abel (Midlands State University, 2019)
The purpose of this study was to assess the impacts of black granite quarrying on household income and food security in Mutoko district. The researcher adopted a case study research design and used two methods of sampling that is purposive sampling and census sampling. Research instruments used were questionnaires, interview guides and an observation check list. Research findings were that black granite quarrying was contributing to household income only to the employed households. Main beneficiaries of increased household income from black granite quarrying were male headed families which were employed in greater numbers compared to female headed families. Quarry salaries had managed to raise the food security status for employed households as households had managed to buy extra food stuff from Harare while other households had purchased farm inputs like fertilisers and maize seeds. However the situation was very different for the non employed households. These are the households who rely on agriculture for accessing food and household income. Quarrying activities like forest clearing was affecting their access to non agricultural sources of food, blasting processes during the excavation stage affected underlying granite rock which had a bearing on availability of underground water necessary for agricultural purposes. In conclusion quarrying is negatively impacting household income and food security in Mutoko district. Some of the recommendations included employment of all the locals who were affected by the land eviction process and raising salaries for locals.